2017
DOI: 10.7861/clinmedicine.17-1-48
|View full text |Cite
|
Sign up to set email alerts
|

Delirium: a guide for the general physician

Abstract: Delirium describes a sudden onset change in mental status of fluctuating course. This is a state of altered consciousness characterised chiefly by inattention or lack of arousal, but can also include new impairment of language, perception and behaviour. Certain predisposing factors can make an individual more susceptible to delirium in the face of a stressor. Stressors include direct insults to the brain, insults peripheral to the brain or external changes in the environment of an individual. Delirium is varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…No screening of ongoing research protocols was performed and although the method used was based on a systematic review process, some studies could have been missed. The multifactorial model of delirium already documented, identifying predisposing and precipitating triggers, 2,79 has been used to categorise factors associated with delirium, thus using mainly a conservative-deductive approach. Moreover, according to the nature of scoping reviews, which are substantially used to map the research available, the studies included were not evaluated for their methodological quality, as suggested by Moja et al 80…”
Section: Limitationsmentioning
confidence: 99%
“…No screening of ongoing research protocols was performed and although the method used was based on a systematic review process, some studies could have been missed. The multifactorial model of delirium already documented, identifying predisposing and precipitating triggers, 2,79 has been used to categorise factors associated with delirium, thus using mainly a conservative-deductive approach. Moreover, according to the nature of scoping reviews, which are substantially used to map the research available, the studies included were not evaluated for their methodological quality, as suggested by Moja et al 80…”
Section: Limitationsmentioning
confidence: 99%
“…Over the age of 80 years, more than one third of those in hospital will experience delirium. 2 The cause of delirium is typically multifactorial. In fact, the development of delirium involves the complex interrelationship between a vulnerable patient (with a predisposing factor) and exposure to precipitating factors or noxious insults.…”
Section: Introductionmentioning
confidence: 99%
“…And precipitating factors such as: Drugs, primary neurologic diseases, infections, severe acute illness, dehydratation, surgery, use of physical restraints, use of catheters. [1][2][3]…”
Section: Introductionmentioning
confidence: 99%
“…1 It would seem at long last there is a plan to simplify the greatly criticised 'tick-box approach' to medical training. This is hardly a new idea and this progress has been greatly hampered and delayed by the Joint Royal Colleges of Physicians Training Board (JRCPTB) themselves.…”
Section: The New Uk Internal Medicine Curriculummentioning
confidence: 99%